2014
DOI: 10.1093/molehr/gau053
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic mechanisms regulate placental c-myc and hTERT in normal and pathological pregnancies; c-myc as a novel fetal DNA epigenetic marker for pre-eclampsia

Abstract: Placental development is known for its resemblance with tumor development, such as in the expression of oncogenes (c-myc) and telomerase (hTERT). The expression of c-myc and hTERT is up-regulated during early pregnancy and gestational trophoblastic diseases (GTDs). To determine the role of DNA methylation [via methylation-sensitive high resolution melting (MS-HRM)] and histone modifications [via chromatin immunoprecipitation (ChIP assay)] in regulating the differential expression of c-myc and hTERT during norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 71 publications
1
39
0
Order By: Relevance
“…Earlier studies have reported the expressions of MMP2 and MMP9 within the first-trimester placenta (StaunRam & Shalev 2005), whereas high expression levels of MMP2 and MMP9 have been observed in highly invasive extravillous trophoblasts (Seval et al 2004). Our previous study (Rahat et al 2014) and few recent studies (Dokras et al 2006, Rahnama et al 2006 have highlighted the importance of epigenetic mechanisms in the regulation of gene expression during placentation. Therefore, we aimed to find the significance of differential mRNA expressions and the epigenetic regulatory mechanisms of MMP2 and MMP9 and their inhibitors in the development of pathological pregnancies, with reference to normal physiological pregnancies.…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…Earlier studies have reported the expressions of MMP2 and MMP9 within the first-trimester placenta (StaunRam & Shalev 2005), whereas high expression levels of MMP2 and MMP9 have been observed in highly invasive extravillous trophoblasts (Seval et al 2004). Our previous study (Rahat et al 2014) and few recent studies (Dokras et al 2006, Rahnama et al 2006 have highlighted the importance of epigenetic mechanisms in the regulation of gene expression during placentation. Therefore, we aimed to find the significance of differential mRNA expressions and the epigenetic regulatory mechanisms of MMP2 and MMP9 and their inhibitors in the development of pathological pregnancies, with reference to normal physiological pregnancies.…”
Section: Introductionmentioning
confidence: 67%
“…Cytotrophoblasts were isolated from first-trimester placentas (6-11 weeks) by enzymatic digestion of first-trimester villi as explained previously (Rahat et al 2014). Briefly, 2 g dissected first-trimester villi was subjected to sequential trypsin digestion.…”
Section: Isolation Of Cytotrophoblast From First-trimester Villimentioning
confidence: 99%
See 2 more Smart Citations
“…Thereafter, MS-HRM was performed as described by Rahat et al [30]. In order to prepare standard curve for the determination of percentage methylation of the CpG islands present within the promoter region of folate transporters, methylated standards were used that ranges from 0 to 100 %.…”
Section: Methylation Sensitive High Resolution Melting Pcr (Ms-hrm)mentioning
confidence: 99%